2011
DOI: 10.1111/j.1526-100x.2010.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Hay Transfer Promotes Establishment of Mediterranean Steppe Vegetation on Soil Disturbed by Pipeline Construction

Abstract: International audienceThe Coussouls de Crau Nature Reserve is a xeric steppe providing a habitat for remarkable animals. Over the past centuries, this steppe has been partly destroyed and fragmented and has been reduced to 9,500 ha out of the 55,000 ha existing before the 16th century. Although this ecosystem is protected, 23 ha of natural habitat were nonetheless destroyed in 2006 during the construction of an underground pipeline. To mitigate potential future damage, an original experiment in restoration eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 53 publications
1
34
1
1
Order By: Relevance
“…In fact, this steppe vegetation is the result of a regime of particular stress and disturbance induced by the shallow red Mediterranean soil (red fersialitic soil) and by the Mediterranean climate interacting with centuries of sheep grazing and a succession of prairie fires (Devaux et al, 1983;Cherel, 1988;Badan et al, 1995;Henry, 2009). Although this environment is partly protected through the establishment of a National Natural Reserve in 2001 on 7400 ha, extensive areas today require active restoration Coiffait-Gombault et al, 2011;Jaunatre et al, 2014a) as recovery of the steppe vegetation after changes in land use is extremely slow (Römermann et al, 2005;Dutoit et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 98%
“…In fact, this steppe vegetation is the result of a regime of particular stress and disturbance induced by the shallow red Mediterranean soil (red fersialitic soil) and by the Mediterranean climate interacting with centuries of sheep grazing and a succession of prairie fires (Devaux et al, 1983;Cherel, 1988;Badan et al, 1995;Henry, 2009). Although this environment is partly protected through the establishment of a National Natural Reserve in 2001 on 7400 ha, extensive areas today require active restoration Coiffait-Gombault et al, 2011;Jaunatre et al, 2014a) as recovery of the steppe vegetation after changes in land use is extremely slow (Römermann et al, 2005;Dutoit et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 98%
“…First, the high occurrence of annual species and patchy distribution of serpentine habitat among a nonserpentine matrix is well-suited to testing spatial questions (26) with the hay transfer method (23). Second, our study took place in the California Floristic Province, a global biodiversity hotspot that is threatened by the pervasive invasion of European grasses (26,27).…”
Section: Significancementioning
confidence: 99%
“…We tested the spatial scales at which dispersal and environmental heterogeneity impose constraints on species distributions and diversity using a "hay transfer" technique (23) in serpentine annual plant communities in California. This technique involved vacuuming the seed bank and other loose material from field plots, pooling the material among plots, and then redistributing it.…”
Section: Significancementioning
confidence: 99%
“…Soil compaction and topsoil removal during oil pipeline construction resulted in significant decreases in soil organic matter and nitrogen and phosphorous contents (Woodward 1996). Coiffait-Gombault et al (2011) reported that pipeline construction affected soil C/N, pH, and CaO.…”
Section: Introductionmentioning
confidence: 99%